Translation of the 5D Itching Scale from English to Malay, and Its Validation among Patients with Chronic Kidney Disease in Malaysia - Rehman, Inayat Ur; Wu, David Bin-Chia; Pauline Lai, Siew Mei; Palanisamy, Uma Devi; Lim, Soo Kun; Khan, Tahir Mehmood (Frontiers in Medicine, 2017)
Introduction: Several tools have been developed to assess the severity of pruritus. In Malaysia, no tool has been validated to assess pruritus in patients with chronic kidney disease (CKD). Therefore, the aim of our study was to validate the Malay 5D itching scale (M5D-IS) among patients with CKD in Malaysia. Method: The English version of the 5D-IS was translated into Malay according to International Guidelines. Face and content validity was determined by an expert panel and pilot tested in patients with end stage renal disease (ESRD). The M5D-IS was then validated in a tertiary hospital in Malaysia from May to June 2016. We recruited patients with (i.e. patients with ESRD) and without pruritus (i.e. patients with stage 1-3 CKD) (to determine if the M5D-IS could discriminate between the two groups), and administered the M5D-IS at baseline and 2 weeks later. Exploratory factor analysis was used to examine the construct validity. Internal consistency was assessed using Cronbach’s alpha and intraclass correlation coefficient was calculated to assess the reliability of the instrument. Results: A total of 70 participants were recruited (response rate=100%). The majority were male (51.4%), and Malay (67.1%). Exploratory factor analysis revealed that the 5D-IS had 2-factor loadings: “daily routine activity” and “pattern of itching”, which explained 77.7% of the variance. The overall score of the M5D-IS, as well as for each domain, was significantly worse in participants with pruritus (9.83±0.35), compared to those without pruritus (5.51±0.93, p<0.001). The overall Cronbach’s alpha for the M5D-IS was (0.861), indicating adequate internal consistency. At test-retest, the intraclass correlation coefficient was significantly correlated. Conclusion: The M5D-IS was found to be a valid and reliable instrument to assess pruritus among patients with CKD in Malaysia.